Half broke horses : a true-life novel - Walls, Jeannette (New York : Scribner, 2009)
For the first 10 years of her life, Lily Casey Smith, the narrator of this true-life novel by her granddaughter, Walls, lived in a dirt dugout in west Texas. Walls, whose megaselling memoir, The Glass Castle, recalled her own upbringing, writes in what she recalls as Lily's plainspoken voice, whose recital provides plenty of drama and suspense as she ricochets from one challenge to another. Having been educated in fits and starts because of her parents' penury, Lily becomes a teacher at age 15 in a remote frontier town she reaches after a solo 28-day ride. Marriage to a bigamist almost saps her spirit, but later she weds a rancher with whom she shares two children and a strain of plucky resilience. (They sell bootleg liquor during Prohibition, hiding the bottles under a baby's crib.) Lily is a spirited heroine, fiercely outspoken against hypocrisy and prejudice, a rodeo rider and fearless breaker of horses, and a ruthless poker player. Assailed by flash floods, tornados and droughts, Lily never gets far from hardscrabble drudgery in several statesNew Mexico, Arizona, Illinoisbut hers is one of those heartwarming stories about indomitable women that will always find an audience.
Keywords: Smith, Lily Casey, -- 1901-1968 -- Fiction; Autobiographical fiction